High amylose to amylopectin ratios in nitrogen-free diets decrease the ileal endogenous amino acid losses of broiler chickens - Zhou, Huajin; Mahmood, Tahir; Wu, Wei; Chen, Yanhong; Yu, Yao; Yuan, Jianmin (Animal Nutrition, 2023)
This study explored the variation of ileal endogenous amino acid (IEAA) losses and its influencing factors in chickens offered nitrogen-free diets (NFD) containing different ratios of amylose to amylopectin (AM/AP). A total of 252 broiler chickens at 28 d old were randomly allocated into 7 treatment groups for a 3-d trial. The dietary treatments included a basal diet (control), a NFD containing corn starch (CS), and 5 NFD with AM/AP ratios of 0.20, 0.40, 0.60, 0.80, and 1.00, respectively. As the AM/AP ratio increased, the IEAA losses of all AAs, starch digestibility and maltase activity linearly decreased (P < 0.05), but the DM digestibility linearly and quadratically decreased (P < 0.05). Compared with the control, the NFD increased the number of goblet cells and its regulatory genes mucin-2 and krüppel-like factor 4 (KLF-4) while decreasing serum glucagon and thyroxine concentrations, ileal villus height, and crypt depth (P < 0.05). Additionally, NFD with lower AM/AP ratios (0.20 and 0.40) decreased the ileal microbiota species richness (P < 0.05). In all NFD groups, the number of Proteobacteria increased whereas the abundance of Firmicutes dropped (P < 0.05). However, the broilers in the AM/AP 0.60 group were closer to the digestive physiological state of chickens fed the control diet, with no significant change in maltase activity and mucin-2 expression (P < 0.05). In conclusion, increasing AM/AP ratio in a NFD decreased the IEAA losses and the apparent ileal digestibility of starch but inevitably resulted in malnutrition and disruption of gut microbiota homeostasis. This study recommends AM/AP in NFD at 0.60 to measure IEAA of broiler chickens.